Are proton pump inhibitors over‐prescribed in infants?. (December 2014) - Ditty, Annabelle; Garg, Alka; Leggett, Catherine; Turner, Sean
Abstract: Background: The use of proton pump inhibitors (PPIs) for the off‐label treatment of gastro‐oesophageal reflux and 'colic' in infants has become of increasing interest in the medical community and mass media. Concerns are now being raised about whether PPI are overused in infants as the evidence for efficacy is lacking and there are concerns about long‐term adverse effects. Aim: To assess the extent and indications for prescribing of PPIs in infants, in a tertiary paediatric hospital. Method: Two audits were undertaken (1) a retrospective audit of dispensing data for PPIs over 10 years from 2002 to 2011 to assess prescribing patterns in infants, and (2) a prospective audit investigating the use of orally administered PPI and management of gastro‐oesophageal reflux in admitted infants. Results: Dispensing data showed an increase in prescribing of omeprazole to infants from 2002 to 2009, with a subsequent decrease. The prospective audit included 21 patients with 16 interviews being performed. Of the 21 patients, 12 were treated for an indication relating to reflux and general irritability such as back arching, crying or being unsettled. Conclusion: The prospective results indicate that PPIs are generally being used appropriately in patients with oesophagitis, receiving treatment with steroids, and haematemesis. However, PPIs were also being prescribed as a last resort to treat 'normal' infant behaviour such as crying, back arching and spilling. This use should be discouraged. The retrospective audit shows that prescribing PPIs for infants had decreased over the last 24 months.